Origin, Impact, and Reaction to Misogynistic Behaviors: An Interview with Kate A. Manne, PhD - Lopez, Brianna; Manne, Kate A. (Stance: an international undergraduate philosophy journal, 2021)
Kate A. Manne is an associate professor at the Sage School of Philosophy at Cornell University, where she has been teaching since 2013. Before that, she was a junior fellow at the Harvard Society of Fellows (2011–2013), did her graduate work at MIT (2006–2011), and was an undergraduate at the University of Melbourne (2001–2005), where she studied philosophy, logic, and computer science. Her current research is primarily in moral, feminist, and social philosophy. She is the author of two books, including her first book Down Girl: The Logic of Misogyny and her latest book Entitled: How Male Privilege Hurts Women. Manne has also published a number of scholarly papers about the foundations of morality, and she regularly writes opinion pieces, essays, and reviews in venues—including The New York Times, The Boston Review, the Huffington Post, and the Chronicle of Higher Education.